The Spatial Decay of Human Capital Externalities - A Functional Regression Approach with Precise Geo-Referenced Data - Johann Eppelsheimer; Christoph Rust (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
This paper analyzes human capital externalities from high-skilled workers by applying functional regression to precise geocoded register data. Functional regression enables us to describe the concentration of high-skilled workers around workplaces as continuous curves and to efficiently estimate a spillover function that depends on distance. Furthermore, our rich panel data allow us to address the sorting of workers and to disentangle human capital externalities from supply effects by using an extensive set of time-varying fixed effects. Our estimates reveal that human capital externalities attenuate with distance and disappear after 15 kilometers. Externalities from the immediate neighborhood are twice as large as those from surroundings ten kilometers away. – – Wir analysieren Humankapitalexternalitäten von Hochqualifizierten mit präzisen georeferenzierten Sozialversicherungsdaten. Functional Regression ermöglicht es uns die Konzentration von Hochqualifizierten um Arbeitsplätze herum als kontinuierliche Kurven zu beschreiben und eine von der Entfernung abhängige Spillover-Funktion zu schätzen. Unsere umfangreichen Paneldaten ermöglichen es uns außerdem räumliche Selektion von Beschäftigten zu berücksichtigen und Humankapitalexternalitäten von Angebotseffekten mittels hochdimensionaler Fixed-Effects zu trennen. Unsere Schätzungen zeigen, dass Humankapitalexternalitäten mit der Distanz abnehmen und etwa 15 Kilometer weit reichen. Humankapitalexternalitäten aus der unmittelbaren Nachbarschaft sind doppelt so hoch wie solche aus zehn Kilometern Entfernung.
Keywords: C13; D62; J24; J31; R10; R12; 330; human capital externalities; functional regression; geodata; wages